Composition of Chemical Elements in Edible Offal and Muscle of Semi- extensively Reared Indigenous Doom Pig Breed of Northeast India and its Correlation with Feed and Environment - Daimari, Rijumoni; Narzari, Silistina; Sarmah, Jatin (Journal of Advanced Veterinary Research, 2022)
With the increase in anthropogenic activities and other long-range transport of pollutants, there is a high probability of accumulation of heavy metals in foods consumed by pigs which in turn may amass in edible offals. Therefore, the present study was undertaken to evaluate sixteen chemical (heavy and non-heavy) elements in edible offal and longissimus dorsi muscle of indigenous Doom pig breed of India. Additionally, the values for highly toxic elements were compared with maximum residue limits (MRLs) stated by the regulatory authorities. The elements namely- Sodium (Na), Magnesium (Mg), Potassium (K), Calcium (Ca), Manganese (Mn), Iron (Fe), Zinc (Zn), Selenium (Se), Copper (Cu), Cobalt (Co), Chromium (Cr), Nickel (Ni), Arsenic (As), Cadmium (Cd), Mercury (Hg) and Lead (Pb) were determined in the tissues as well as in feed, drinking water and soil by Inductively Coupled Plasma-Optical Emission Spectrometry. Among the elements determined, the non-heavy metals (K, Na, Mg and Ca) were found to be the highest both in tissues (edible offal and muscle) and feed, drinking water and soil followed by Fe, Zn and Mn which are essential heavy metals. Ni was found to exceed the European Food Safety Agency allowed limits. Spearman correlation test shows significantly (p<0.0001) positive relationships between the element of tissues and feed, drinking water and soil. The work underscores the elemental analysis on hitherto understudied consumable edible offal for value addition to the food industry.